2003
DOI: 10.1191/0961203303lu499oa
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic resonance imaging in neuropsychiatric systemic lupus erythematosus

Abstract: Neuropsychiatric symptoms are common in systemic lupus erythematosus (SLE) but are poorly understood. Although there is a wide spectrum of clinical manifestations, brain histology often simply shows a bland vasculopathy. Magnetic resonance techniques such as magnetic resonance spectroscopy, magnetization transfer imaging and diffusion weighted imaging have been used to try to improve our understanding of the pathophysiological mechanisms involved in neuropsychiatric lupus (NPSLE). This article reviews the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 41 publications
(42 reference statements)
0
19
1
4
Order By: Relevance
“…This technique shows four major spectra corresponding to different metabolites: N-acetylaspartate, which can be considered a marker of neuronal integrity; choline, including choline containing phospholipids that are released during active myelin breakdown; creatine, which has a constant concentration throughout the brain and tends to be resistant to change in all but the most severely destructive lesions (therefore is suitable for use as an internal standard against which the resonance intensities of NAA and choline can be normalised); and lactate (Lac), which is the end product of glycolysis and accumulates when oxidative metabolism cannot meet energy requirements. 15 Brain 1 H-MRS has been carried out in SLE patients with encouraging results. 12-15 31 Concerning single metabolites, previous quantitative studies have shown that NAA is substantially reduced both in patients with active NP-SLE and in SLE patients with a past history of NP-SLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique shows four major spectra corresponding to different metabolites: N-acetylaspartate, which can be considered a marker of neuronal integrity; choline, including choline containing phospholipids that are released during active myelin breakdown; creatine, which has a constant concentration throughout the brain and tends to be resistant to change in all but the most severely destructive lesions (therefore is suitable for use as an internal standard against which the resonance intensities of NAA and choline can be normalised); and lactate (Lac), which is the end product of glycolysis and accumulates when oxidative metabolism cannot meet energy requirements. 15 Brain 1 H-MRS has been carried out in SLE patients with encouraging results. 12-15 31 Concerning single metabolites, previous quantitative studies have shown that NAA is substantially reduced both in patients with active NP-SLE and in SLE patients with a past history of NP-SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Altered metabolite ratios have been observed even in the absence of MRI lesions but up to now few studies have been carried out in SLE patients with and without overt neurological involvement. [11][12][13][14][15] In a previous preliminary study using a multi-imaging coregistration approach, we found a topographic correlation between SPECT and metabolic abnormalities detected with 1 H-MRS in the absence of MRI lesions in two SLE patients. 16 Our aim in the present report was to verify-in a further six patients with SLE but without clinical evidence of major CNS involvement-whether perfusion defects detected by SPECT in areas free of MRI abnormalities correspond to areas of neuronal metabolic impairment detected by 1 H-MRS and, if so, whether such alterations can predict the appearance of new lesions detectable by MRI.…”
mentioning
confidence: 85%
“…The possibility of being able to differentiate inflammatory lesions from ischemic damage with DWI is very promising (Peterson et al 2003). DWI-DTI may be useful in differentiating ischemia associated with SLE-APS from inflammatory lesions and indeed from MS. A recent study used DTI to quantify the extent of occult injury of the cervical region of the spinal cord in 11 NP-SLE patients and 10 healthy controls (Benedetti et al 2007).…”
Section: Brain Imaging Findings In Slementioning
confidence: 99%
“…These changes were found not only within focal brain lesions but also in normal appearing white matter. [9][10][11] PWI is an MR technique that enables measurements of hemodynamics of cerebral microcirculation with the use of the cerebral blood volume (CBV) parameter. The value of CBV correlates with vessel density and is found to be lower in hypoperfused brain areas.…”
Section: Introductionmentioning
confidence: 99%